2022
DOI: 10.1002/ardp.202200224
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new N‐(3‐oxo‐1‐thia‐4‐azaspiro[4.5]decan‐4‐yl)pyridine‐3‐carboxamide derivatives and evaluation of their anti‐influenza virus and antitubercular activities

Abstract: We here report the synthesis, structural characterization, and evaluation of the antiviral and antitubercular activities of a novel series of hybrid spirothiazolidinone derivatives (2a–f and 3a–f) containing the nicotinohydrazide moiety, which is an isomer form of the approved antitubercular drug isoniazid. When evaluated for activity against influenza A/H1N1, A/H3N2, and B viruses, three of the new compounds proved to possess specific antiviral activity against the influenza A/H3N2 virus. The most active anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The results showed that the imidazo[2,1-b][1,3]thiazole moiety could be replaced by 2-hydroxyphenyl (Figure 9B), 1-adamantyl (Figure 9C), or 5-chloro-2-hydroxyphenyl (Figure 9D), as the antiviral efficacy and selectivity were not drastically diminished [76][77][78]. Recent studies also showed the feasibility of incorporating an indole moiety, leading to a compound (Figure 9E) that showed an EC 50 of 1 nmol/L in H3N2 virus-infected MDCK cells [79]. Docking calculations performed using the THBQ-and arbidol-bound complexes with HA showed that this latter compound adopts similar binding poses, with the azaspiro group being inserted into the hydrophobic pocket and the indole group oriented towards the pocket mouth.…”
Section: Spirothiazolidinone Derivativesmentioning
confidence: 99%
“…The results showed that the imidazo[2,1-b][1,3]thiazole moiety could be replaced by 2-hydroxyphenyl (Figure 9B), 1-adamantyl (Figure 9C), or 5-chloro-2-hydroxyphenyl (Figure 9D), as the antiviral efficacy and selectivity were not drastically diminished [76][77][78]. Recent studies also showed the feasibility of incorporating an indole moiety, leading to a compound (Figure 9E) that showed an EC 50 of 1 nmol/L in H3N2 virus-infected MDCK cells [79]. Docking calculations performed using the THBQ-and arbidol-bound complexes with HA showed that this latter compound adopts similar binding poses, with the azaspiro group being inserted into the hydrophobic pocket and the indole group oriented towards the pocket mouth.…”
Section: Spirothiazolidinone Derivativesmentioning
confidence: 99%